O PLANEJAMENTO GOVERNAMENTAL E SEUS REFLEXOS NA ESTRUTURA FUNDIÁRIA DE MATO GROSSO - Alves Jr., Gilberto Torres (Caminhos de Geografia, 2003)
The aim of this work is to analyse the land property structures of State of Mato Grosso after Superintendência do Desenvolvimento do Centro-Oeste - SUDECO has planned the development of the Brazilian midle-west region in the 70's and 80's in order to occupate the empty demographics areas and integrate it to the south and southeast economical process.